Backfill-strip mining and CO2 mineralization sequestration in coal mine goaves: A synergetic method and its key technologies - Mengbo ZHU; Lang LIU; Shuangming WANG; Baoning WEI; Ruoyu RONG; Wenzhong ZHANG; Dengdeng ZHUANG; Qifeng JIA (Meitian dizhi yu kantan)
ObjectiveCoals serve as both the cornerstone of China’s energy security and important industrial raw materials. However, their mining and utilization tend to cause ecological and environmental problems such as CO2 emissions, the generation of solid wastes, and land subsidence. This necessitates reforming coal mining methods to promote the green, low-carbon, and sustainable development of China’s coal industry.MethodsThrough the comparative analysis of the conditions of CO2 sequestration in goaves corresponding to the caving, room-and-pillar (also known as knife-pillar), and backfill mining methods, this study developed a synergetic method for backfill-strip mining and CO2 mineralization sequestration in goaves by combining the current status of technologies for geologic CO2 sequestration and coal mine backfill mining. With a typical coal mine in Shaanxi Province as a case study, this study conducted numerical simulation experiments on damage to the overlying low-permeability, thick mudstone layer during backfill-strip mining. Based on the continuous and the foundation beam models, this study established a mechanical model of the cap rocks and a model for the mining-induced fracture heights. Additionally, key technologies for the synergetic method were proposed.Results and ConclusionsGoaves formed under the caving and room-and-pillar mining are characterized by poor reservoir and cap rock conditions for CO2 storage, which tend to pose high leakage risks. In contrast, the backfill mining method can effectively protect cap rock integrity. However, it is necessary to reserve storage spaces if this method is applied. The numerical simulation results indicated that the maximum subsidence of the upper boundary of the low-permeability, thick mudstone layer No.3 above the goaf were determined at 1 230 mm, 520 mm, and 105 mm, respectively under backfilling rates of 0, 50%, and 80%. As the backfilling rate increased, the low-permeability, thick mudstone layer exhibited decreased subsidence amplitude and substantially reduced plastic deformation areas. Therefore, the integrity of the cap rocks can be ensured by optimizing the process and parameters of the strip-backfill mining. The mechanical model of a non-horizontal continuous beam with six spans under the condition of three mining-backfilling cycles was established, and the expressions for reaction forces and bending moments at pivot points were derived. Additionally, the model for the mining-induced fracture heights was constructed. To achieve the practical application of the synergetic method, it is necessary to make breakthroughs in key technologies including geological siting, the building and stability-orientated regulation of underground gas storage (UGS) facilities for CO2 sequestration, CO2 mineralization combined with desulfurization/denitrification for backfilling material preparation, and CO2 charging simulation and optimization, followed by the development of comprehensive schemes. This will offer new approaches for the green, low-carbon development of China’s coal industry.